2001
DOI: 10.1046/j.1440-169x.2001.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of sequential expression of the organizer‐related genes in normal Cynops pyrrhogaster embryos and mesodermalized ectoderm

Abstract: An artificially mesodermalized ectoderm (mE) of early Cynops pyrrhogaster gastrula acquires the organizer property; the mE is able to induce the secondary axis. The expression of organizer-related genes was investigated during the mesodermalizing process of the mE. The expression of C. pyrrhogaster organizer-related genes, such as bra, gsc, lim-1, chd and noggin, were analyzed. Cynops pyrrhogaster shh expression was also investigated. The organizer-related genes were activated by 12 h after the mesoderm-induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2002
2002
2007
2007

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
0
5
0
2
Order By: Relevance
“…In Cynops embryos, gsc and bra genes are expressed during the mesodermalizing process (Sone et al 1997;Yokota et al 1998;Tabata et al 2001;Kaneda et al 2002). It has been indicated that bra is not expressed at the early gastrula stage, but its expression is detected in the area corresponding to the prospective notochord of the advanced gastrula (Sone et al 1997;Yokota et al 1998;Doi et al 2000;Tabata et al 2001). Neither invagination nor involution movements were observed in the suramin-treated gastrulae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Cynops embryos, gsc and bra genes are expressed during the mesodermalizing process (Sone et al 1997;Yokota et al 1998;Tabata et al 2001;Kaneda et al 2002). It has been indicated that bra is not expressed at the early gastrula stage, but its expression is detected in the area corresponding to the prospective notochord of the advanced gastrula (Sone et al 1997;Yokota et al 1998;Doi et al 2000;Tabata et al 2001). Neither invagination nor involution movements were observed in the suramin-treated gastrulae.…”
Section: Discussionmentioning
confidence: 99%
“…To compare the expressions of gsc , bra , α‐actin and N‐CAM , the total RNA extracted from one embryo of each sample was used for reverse transcription (RT)–polymerase chain reaction (PCR). Total RNA isolation and RT–PCR have been previously described (Tabata et al . 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea is supported both by the delayed determination of the notochord with respect to the onset of gastrulation, in urodeles compared with anurans (Kaneda and Suzuki, '83;Sakaguchi et al, 2002) and by the delayed onset of Brachyury expression in Cynops (Sone et al, '97;Yokota et al, '98;Tabata et al, 2001) and Ambystoma (Johnson et al, 2003) after the beginning of gastrulation, compared with its earlier expression in Xenopus (Smith et al,'91). Perhaps this reflects a more progressive mode of patterning, with only the currently more vegetal population of cells in the portion of the marginal zone that has not yet ingressed receiving signals for specification and cell behavior.…”
Section: Example 3: Regulation Of Subduction Vs Mibmentioning
confidence: 97%
“…For example, the initial symmetry breaking mechanism giving rise to the embryonic dorsal-ventral axis (Elinson and Rowning, '88;Houliston and Elinson, '91;Iwao et al, '97;Elinson and Ninomiya, 2003;Weaver and Kimelman, 2004;Heasman, 2006), the expression of Brachyury in presumptive mesoderm before involution, and in the extending notochord after involution (Smith et al, '91;del Pino, '96;Tabata et al, 2001;Kaneda et al, 2002;Johnson et al, 2003;Moya et al, 2007) and the expression of Lim1 in the organizer (Taira et al, '92;Tabata et al, 2001;Kaneda et al, 2002;Hukriede et al, 2003;Langeland et al, 2006;del Pino et al, 2007) are all well conserved among the anurans and urodeles. In some cases the conservation of patterning also seems to translate to the conservation of the spatio-temporal pattern of cell behaviors, as noted above for MIB and Subduction.…”
Section: Modules and Their Interactionsmentioning
confidence: 99%